Anatomical reconstruction of the anterior inferior tibiofibular ligament in elite athletes using InternalBrace suture tape. (1st January 2022) - Harris, Nick J.; Nicholson, Gareth; Pountos, Ippokratis
Abstract : Aims: The ideal management of acute syndesmotic injuries in elite athletes is controversial. Among several treatment methods used to stabilize the syndesmosis and facilitate healing of the ligaments, the use of suture tape (InternalBrace) has previously been described. The purpose of this study was to analyze the functional outcome, including American Orthopaedic Foot & Ankle Society (AOFAS) scores, knee-to-wall measurements, and the time to return to play in days, of unstable syndesmotic injuries treated with the use of the InternalBrace in elite athletes. Methods: Data on a consecutive group of elite athletes who underwent isolated reconstruction of the anterior inferior tibiofibular ligament using the InternalBrace were collected prospectively. Our patient group consisted of 19 elite male athletes with a mean age of 24.5 years (17 to 52). Isolated injuries were seen in 12 patients while associated injuries were found in seven patients (fibular fracture, medial malleolus fracture, anterior talofibular ligament rupture, and posterior malleolus fracture). All patients had a minimum follow-up period of 17 months (mean 27 months (17 to 35)). Results: All patients returned to their pre-injury level of sports activities. One patient developed a delayed union of the medial malleolus. The mean return to play was 62 days (49 to 84) for isolated injuries, while the patients with concomitant injuries returned to play in a mean of 104 days (56 to 196). The AOFAS score returned to 100 postoperatively in all patients. Knee-to-wall measurements were the same as the contralateral side in 18 patients, while one patient lacked 2 cm compared to the contralateral side. Conclusion: This study suggests the use of the InternalBrace in the management of unstable syndesmotic injuries offers an alternative method of stabilization, with good short-term results, including early return to sports in elite athletes. Cite this article: Bone Joint J  2022;104-B(1):68–75.